Pediatric asthma and COVID‐19: The known, the unknown, and the controversial - Abrams, Elissa M. (Pediatr Pulmonol, 2020)
The novel coronavirus disease‐2019 (COVID‐19), caused by the pathogen severe acute respiratory syndrome‐CoV‐2, is causing a global pandemic, with over 26.9 million cases and 880,000 deaths as of September 6, 2020. While there has been speculation and observational research about the impact of COVID‐19 on asthma, much remains unknown. The goal of this article is to provide a scoping review on pediatric asthma and COVID‐19 and summarize what we do and do not know from the first wave of the pandemic.